Costs of Persisting Unreliable Memory: Reduced Foraging Efficiency for Free-Flying Parasitic Wasps in a Wind Tunnel - de Bruijn, Jessica A. C.; Vet, Louise E. M.; Smid, Hans M. (Frontiers in Ecology and Evolution, 2018)
Parasitic wasps are known to improve their foraging efficiency after learning of herbivore-induced plant volatiles (HIPVs) upon encountering their hosts on these plants. However, due to spatial and temporal variation of herbivore communities, learned HIPV cues can become unreliable, no longer correctly predicting host presence. Little is known about the potential fitness costs when memories holding such unreliable information persist. Here we studied how persistent memory, containing unreliable information, affects the foraging efficiency for hosts in Cotesia glomerata. Wasps were conditioned to associate one of two types of HIPVs with either P. brassicae frass, 1 single oviposition in P. brassicae, 3 ovipositions in P. brassicae spaced in time or they were kept unconditioned. The following day, wasps were allowed to forage in a wind tunnel, in an environment that either conflicted or was congruent with their learned plant experience. The foraging environment consisted of host (P. brassicae) and non-host (Mamestra brassicae) infested plants. The conflicting environment had non-hosts on the conditioned plant species and hosts on the non-conditioned plant species, whereas the congruent environment had hosts on the conditioned plant species and non-hosts on the unconditioned plant species. Wasps had to navigate through five non-host infested plants to reach the host-infested plant. Since C. glomerata wasps do not distinguish between HIPVs induced by host and non-host caterpillars, the conflicting foraging situation caused a prediction error, by guiding wasps to non-host infested plants. Especially wasps given 3 spaced oviposition experiences, tested in a conflicting situation, spent significantly more time on non-host infested plants and showed a high tendency to oviposit in the non-hosts. As a result, they took significantly more time to find their hosts. Conditioned wasps, which were tested in a congruent situation, were more responsive than unconditioned wasps, but there was no difference in foraging efficiency between these two groups in the wasps that showed a response. We conclude that persistent memories, such as formed after 3 experiences spaced in time, can lead to maladaptive foraging behavior if the contained information becomes unreliable.